Las actitudes de los españoles hacia la reforma del Estado de Bienestar - Del Pino, Eloísa (Política y Sociedad, 2008)
In recent years, it has been asserted that western citizens´ attitudes in support of a powerful Welfare State are less enthusiastic than they were in the past. At present, it is argued, citizens would no longer have a desire for an increase in social expenditures and they would probably not punish a government with retrenchment intentions. In this paper, the hypothesis of a change in citizen’s attitudes toward the Welfare State is explored. The Spanish case is examined using qualitative and quantitative data. The conclusions help to qualify the initial argument. In general, Spaniards’ attitudes in support of a Welfare State based on a strong public sector remain strong and stable, even though certain type of citizens would accept a higher participation of private sector in welfare service provision. Likewise, immigration arises as one of the most discussed issues related with welfare